Two new Brazilian species of Paracerura Deharveng & Oliveira (Collembola: Isotomidae) - de Mendonça, Maria Cleide; Abrantes, Eduardo Assis; Fernandes, Liliane Henriques (Zootaxa, 2009)
Paracerura airesi sp. nov. (Paranã River, State of Tocantins) and P. serrana sp. nov. (Aiuroca Valley, State of Minas Gerais) are described and illustrated. Diagnosis of the genus Paracerura and a comparative table of four known species of the genus are given.